CIVILIAN COMPETENCE OF STUDENT ATHLETES PEDAGOGICAL FEATURES OF DEVELOPMENT - Djumaqulov Shuxrat Baxodirovich, (Research Focus International Scientific Journal, 2025)
This article reveals the importance of the development of civil competence in sports students in a period when professional sports are developing in our country, pedagogical features that ensure the development of civil competence of sports students.